2010
DOI: 10.1002/pssr.201004009
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale piezoresponse of 70 nm poly(vinylidene fluoride‐trifluoro‐ethylene) films annealed at different temperatures

Abstract: In order to characterize the piezoelectric properties of 70 nm thick poly(vinylidene fluoride‐trifluoroethylene), P(VDF‐TrFE), films grown by a spin‐coating technique, both nanoscale manipulation and polarization switching were studied using piezoresponse force microscopy (PFM). We varied the annealing temperature from 75 °C to 145 °C and achieved a high‐quality 70 nm P(VDF‐TrFE) film annealed at the temperature of 95 °C. Ferroelectric domains and their properties were confirmed using X‐ray diffraction, grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Piezo-response force microscopy (PFM) has proven to be a powerful tool to probe the ferroelectric domain structures and polarization switching dynamics at the nanoscale in ferroelectric polymers. 7,[15][16][17][18][19][20][21] In this work, we report the PFM study of the effect of thermal annealing on ferroelectric domain structures in 6 to 20 monolayer (ML) polycrystalline ferroelectric PVDF-TrFE thin films. Stripe-shape domain structures were written at room temperature and subjected to thermal annealing at progressively higher temperatures up to the ferroelectric Curie temperature T C of approximately 110 C. The static configuration of the domain walls (DWs) does not exhibit appreciable changes in characteristics after thermal annealing, showing an temperature-independent roughness exponent f of 0.4-0.5, which is qualitatively different from what has been observed in ferroelectric oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Piezo-response force microscopy (PFM) has proven to be a powerful tool to probe the ferroelectric domain structures and polarization switching dynamics at the nanoscale in ferroelectric polymers. 7,[15][16][17][18][19][20][21] In this work, we report the PFM study of the effect of thermal annealing on ferroelectric domain structures in 6 to 20 monolayer (ML) polycrystalline ferroelectric PVDF-TrFE thin films. Stripe-shape domain structures were written at room temperature and subjected to thermal annealing at progressively higher temperatures up to the ferroelectric Curie temperature T C of approximately 110 C. The static configuration of the domain walls (DWs) does not exhibit appreciable changes in characteristics after thermal annealing, showing an temperature-independent roughness exponent f of 0.4-0.5, which is qualitatively different from what has been observed in ferroelectric oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al [11] demonstrated that films above the melting 2 Advances in Condensed Matter Physics point retain ferroelectric character. Recently, piezoresponse force microscopy is used for nanoscale characterisation of ferroelectric domains and polarization related processes in PVDF-TrFE films annealed below the melting point [13,14]. In this work, nanoscale characterisation of the morphology, polarization switching, and local piezoresponse hysteresis loops for PVDF-TrFE films annealed within the range 125 to 180 ∘ C is presented.…”
Section: Introductionmentioning
confidence: 99%
“…To check the ferroelectric phase formation in the films, we conducted X-ray diffraction (XRD) and Fourier transform infrared (FTIR) analysis on P(VDF-TrFE) films with various thicknesses. It is well known that the prominent peak at 2θ = 19.7° is the sum reflections of (110) and (200) planes of the crystalline β phase34. In Fig.…”
Section: Resultsmentioning
confidence: 94%